I'm having trouble with whether Rudin actually proves what he's tried to prove.

Proposition 1.14; (page 6) The axioms of addition imply the following statements:

a) if $x + y = x + z$ then $y = z$

The author's proof is as follows: $ y = (0 + y) = (x + -x) + y = -x + (x + \textbf{y})$ $$ = -x + (x + \textbf{z}) = (-x + x) + z = (0 + z) = z $$

I emphased the section which troubles me. How does Rudin prove that $ y = z $ if he substituted $y = z$?

  • 7
    $\begingroup$ He just used the assumption that $x +y = x + z$. That's why he used associativity (shifted the brackets) in the first place. $\endgroup$
    – Student
    Commented Feb 6, 2017 at 11:05
  • 2
    $\begingroup$ Note that in any proof, you should expect the original assumption to show up somewhere in the proof; otherwise, it would seem that the proof holds without the original assumption, in which case you've proved a tautology. (I.e. when proving $P \implies Q$, if $P$ is not used in your proof, then you've proved that $Q$ is always true.) $\endgroup$ Commented Feb 6, 2017 at 19:07

1 Answer 1


He didn't substitute $z$ for $y$; rather, he substituted $x+z$ for $x+y$. This is legitimate based on the assumption that $x+y = x+z$.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .